Environmental Responsibility, Green Innovation, Firm Value: Asean-5 - Tabah Rizki; Dwi Hartanti (Journal of International Conference Proceedings, 2021)
The purpose of this study was to examine the effect of Environmental Responsibility (ER) and Green Innovation on firm value. Based on stakeholder theory and Resource-Based View (RBV) this study views that Environmental Responsibility (ER) and Green Innovation (GI) are expected to positively affect firm value because they help companies achieve competitive advantage and contribute to sustainable development activities. This study uses a PooledLeast Square (PLS) regression test based on panel data collected from 399 annual reports, sustainability reports from Public Energy and Mining companies listed in ASEAN-5 between 2017 and 2019. The results of the study found that energy and mining companies were proven to increase firm value through the practice of environmental responsibility and green innovation. This research has implications for the community as consumers, it can be taken into consideration to be able to choose which company is responsible for the environment Managers, and other decision makers may need to have a better understanding of the company's behavior in adopting Environmental Responsibility activities and environmentally friendly practices to make the right decisions. Then the government as a regulator can carry out further supervision of companies, especially companies Energy and Mining are in utilizing resources efficiently.